2019
DOI: 10.3390/mps2030075
|View full text |Cite
|
Sign up to set email alerts
|

Large Field Alpha Irradiation Setup for Radiobiological Experiments

Abstract: The use of alpha particles irradiation in clinical practice has gained interest in the past years, for example with the advance of radionuclide therapy. The lack of affordable and easily accessible irradiation systems to study the cell biological impact of alpha particles hampers broad investigation. Here we present a novel alpha particle irradiation set-up for uniform irradiation of cell cultures. By combining a small alpha emitting source and a computer-directed movement stage, we established a new alpha par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…X-ray irradiation was performed using the RS320 (Xstrahl Live Sciences), a self-contained cabinet, with a dose rate of 1.6554 Gy/min and working voltage of 195 kV and 10 mA. Alpha irradiation was performed as described before [46]. In brief, coverslips containing cultured cells were washed with PBS and placed upside down (cells facing down) on a Mylar dish.…”
Section: X-ray and α-Particle Irradiationmentioning
confidence: 99%
“…X-ray irradiation was performed using the RS320 (Xstrahl Live Sciences), a self-contained cabinet, with a dose rate of 1.6554 Gy/min and working voltage of 195 kV and 10 mA. Alpha irradiation was performed as described before [46]. In brief, coverslips containing cultured cells were washed with PBS and placed upside down (cells facing down) on a Mylar dish.…”
Section: X-ray and α-Particle Irradiationmentioning
confidence: 99%
“…Similar observations have been made in cells irradiated with other particles, such as α-particles and carbon ions ( Nagle et al, 2016 ; Roobol et al, 2020 ). 53BP1 foci induced by α-particle are bigger than foci induced by photons ( Roobol et al, 2019 ). Following live dynamics of GFP-tagged 53BP1 foci in α-particle irradiated cells has shown that the repair of DSBs is slower after high LET IR compared to low LET IR.…”
Section: Induction Of Dna Damage By Different Types Of Radiationmentioning
confidence: 98%
“…Plasmid and construct information is available on request. Transfected cells were externally irradiated using previously described methods [34]. Live cell imaging was performed on a confocal microscope (Leica SP5) overnight (16 hours).…”
Section: Confocal (Live Cell) Microscopymentioning
confidence: 99%